Assessing Market Entry Strategies for a Selected Turkish Ceramic Company in the Czech Republic’s Tile Market - Ural, Doğa (2025)
This bachelor's thesis aims to assess the market entrance possibilities of a Turkish ceramic tile company,Kütahya Seramik, into the Czech Republic. The thesis evaluates the appeal and viability of development using strategic models, including PESTEL, SWOT, and competitor analysis. Primary research consists of interviews with architects, interior designer, and the company representative to get a qualitative understanding of local demand and market constraints. Based on the analysis, the study finds that the most practical method for raising brand recognition and competitiveness in the Czech tile market is focused market penetration through localized marketing, enhanced distribution visibility, and strategic partnerships.